2008
DOI: 10.1021/bm8004808
|View full text |Cite
|
Sign up to set email alerts
|

J- and H-Aggregates of 5,10,15,20-Tetrakis-(4-sulfonatophenyl)-porphyrin and Interconversion in PEG-b-P4VP Micelles

Abstract: Micellization of poly(ethylene glycol)-block-poly(4-vinylpyridine) (PEG114-b-P4VP61) induced by 5,10,15,20-tetrakis-(4-sulfonatophenyl)-porphyrin (TPPS) in acidic solutions were studied by dynamic and static light scattering, atomic force microscope, and UV-vis spectroscopy. The resultant complex micelles had a core-shell structure with the electrostatically complex TPPS/P4VP as the core and the soluble PEG as the shell. The anionic TPPS in the micellar core formed J-aggregates at pH 1.5-2.5 and H-aggregates a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(87 citation statements)
references
References 29 publications
2
85
0
Order By: Relevance
“…The average D h of the initial prepared complex micelle at pH 4.0 was 73.5 nm, and the value increased to 111.2 nm accompanied by a broadening in the diameter distribution after adjusting the pH to 1.6. This result was similar to our earlier report [14]. J-aggregates of TPPS possessing side-by-side aggregation type and relative large aggregation number accounts for the larger diameter and broader distribution.…”
Section: Lls Characterization Of the Complex Micellessupporting
confidence: 93%
See 3 more Smart Citations
“…The average D h of the initial prepared complex micelle at pH 4.0 was 73.5 nm, and the value increased to 111.2 nm accompanied by a broadening in the diameter distribution after adjusting the pH to 1.6. This result was similar to our earlier report [14]. J-aggregates of TPPS possessing side-by-side aggregation type and relative large aggregation number accounts for the larger diameter and broader distribution.…”
Section: Lls Characterization Of the Complex Micellessupporting
confidence: 93%
“…We have recently reported that PEG-b-P4VP, possessing aromatic units, resulted in the monomeric form and aggregates of TPPS, and the existence form was strongly depended on the pH and the 4VP/TPPS ratio [14,15]. As reported by Yuya Egawa and coworkers [16], cationic polymers which do not bear aromatic moieties were apt to induce H-aggregation of TPPS.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…In the second stage, when PAA was added the free TPPS monomers in the solution totally self-aggregated to form J-aggregates (side-by-side arrangement) and fewer H-aggregates (face-to-face arrangement), which result from the association of p-conjugated porphyrin rings. [44] At the same time, PAA competed with Ala for binding to the sites (-SO 3 À ) of the formed chiral TPPS aggregates and replaced Ala quickly by the multiple-point electrostatic interaction between amino cations of PAA and peripheral sulfonato anions of the TPPS aggregates. The flexible PAA can easily combine with the chiral TPPS aggregates and twist along the helical direction in which peripheral sulfonato groups of TPPS aggregates arrange, forming the advanced stiff TPPS-PAA complexes.…”
Section: Possible Mechanism For Chiral Memory and Amplification In Tpmentioning
confidence: 99%